Visualidades amazônicas - a fotografia entre o documento e a expressão - MORAES, Rafael Castanheira Pedroso de (2011)
This research aims at discussing the status of the contemporary documentary photography based on both a literature review and an analysis of five photographic series focused on Amazonian area. Those series were produced by three Brazilian photographers: Pedro Martinelli, Claudia Andujar and myself. We conclude that in contemporary photo documentaries a narrowing between reality and fiction can be noticed. The border between the impartial register of the facts and the fiction built over the real has become tenuous. Therefore different proposals of photo documentation have been developed based on the origins of its authors, their habitat, training, visuals references and the cultural practices of their time.